KORELASI ANTARA ASPEK MOTIVASI DALAM PENYUSUNAN ANGGARAN DENGAN EFEKTIVITAS PELAKSANAAN PROGRAM KEGIATAN PADA PEMERINTAHAN PROVINSI NANGGROE ACEH DARUSSALAM - Basri Zein; Nelly Dikkifiana (Jurnal Telaah dan Riset Akuntansi, 2008)
This objective of research is aimed at finding out the correlations of motivation aspects  in budget arrangement and effectiveness of program imple-mentation of the Provincial Government of Nanggroe Aceh Darussalam. Motivation aspects consist of working achievement, degree of complications on budgeting, degree of fairness on budgeting, and style of leadership.The samples comprice 100 employees selected by using simple random sampling. The data were collected by questionnaires, which have been tested both for its validity and for reliability. The Product Moment Correlation is used to test the validity of the data with the degree of significance 0.05 while the reliability is tested by using Alpha Cronbach technique.The result of this research shows that: (1) t test by partial degree of complication variable and degree of fairness variable has a significant correlation on effectiveness of program implementation. Style of leadership variable by partial also has significant correlation on effectiveness of program implementation, but working achievement variable has no significant correlation on effectiveness of program implementation.  (2) there is positive correlation between four independent variables and dependent variable. (3) coefficient correlation shows that correlation between dependent variables and independent variable is 0.465. (4) R square is 0.12, indicates that there is 88% other aspects influence effectiveness of program implementation of the provincial government of Nanggroe Aceh Darussalam. Keywords : working achievement, degree of complications, degree of fairness, style of leadership